Pengaruh Brand Image, Brand Awareness, Dan Kualitas Produk Terhadap Keputusan Pembelian Produk: (Studi Pada Merek H&M Di Solo Solo Paragon Mall) - Wahyudin Noor; Robby Andika Kusumajaya; Myra Andriana; Haryo Kusumo; Bambang Widjanarko Susilo (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to determine and analyze the direct influence of brand image on purchasing decisions for H&M brand products at Solo Paragon Mall, to determine and analyze the direct influence of brand awareness on purchasing decisions for H&M brand products at Solo Paragon Mall, to determine and analyze the direct influence of product quality on purchasing decisions for H&M brand products at Solo Paragon Mall and to determine and analyze the simultaneous influence of brand image, brand awareness and product quality on purchasing decisions for H&M brand products at Solo Paragon Mall. This study uses a quantitative method with a sample size of 100 H&M brand consumer respondents. Data were analyzed using multiple linear regression analysis tests. The results of the study indicate that brand image directly has a significant effect on purchasing decisions for H&M brand products at Solo Paragon Mall, brand awareness directly has a significant effect on purchasing decisions for H&M brand products at Solo Paragon Mall, product quality directly has a significant effect on purchasing decisions for H&M brand products at Solo Paragon Mall, and brand image, brand awareness and product quality directly and simultaneously have a significant effect on purchasing decisions for products at Solo Paragon Mall.